(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
After a brief introduction to dialysis in general and on the needs of a dialysis patient, the contribution focuses on the use of shared care planning instruments for this group of patients. It highlights that in some circumstances, for a dialysed patient, a limitation of medical treatments could be more appropriate and could avoid exposing patients to risks and side effects. To this end, broader and more frequent use of advanced care planning instruments to cope in the building of the doctor-patient relationship, and with the équipe. Conclusions present the experience of the Trento Health Authority and the perspective to increase the use of ACP.